The connection of hyper lattice implication algebras and related hyper algebras - Shokoofeh Ghorbani (Journal of Hyperstructures, 2016)
In this paper, we de ne the concepts of (good) con- gruences and strong congruences on hyper lattice implication alge- bras and use them to construct quotient hyper lattice implication algebras. We describe the relations between hyper lattice implica- tion algebra and hyper MV-algebra, hyper K-algebra, (weak) hyper residuated lattices.